Premature aging in genetic diseases: what conclusions can be drawn for physiological aging - Milosic, Filip; Hengstschläger, Markus; Osmanagic-Myers, Selma (Frontiers in Aging, 2024)
According to current views the major hallmarks of physiological aging may be subdivided into three categories, primary causes of cellular damage (genomic instability, telomere attrition, loss of proteostasis epigenetic alterations and compromised macroautophagy), antagonistic hallmarks that represent response to damage (deregulated nutrient sensing, cellular senescence, mitochondrial dysfunction) and integrative hallmarks that represent culprits of the phenotype (stem cell exhaustion, altered intercellular communication, chronic inflammation, dysbiosis). In contrast to physiological aging, premature aging diseases are driven by one or two distinct primary causes of aging, such as genomic instability in the case of Werner syndrome (WS), each displaying other hallmarks of aging to a variable extent. In this review we will focus on primary causes of well-investigated premature aging diseases Hutchinson-Gilford progeria syndrome (HGPS), WS, and Cockayne syndrome (CS) and for each provide an overview of reported aging hallmarks to elucidate resemblance to physiological aging on the mechanistic level and in the context of characteristic age-related diseases. Ubiquitous and tissue specific animal models of premature aging diseases will be discussed as useful tools to decipher fundamental aging-related mechanisms and develop intervention strategies to combat premature aging and age-related diseases.